2011
DOI: 10.1007/s11802-011-1801-x
|View full text |Cite
|
Sign up to set email alerts
|

Cloning, expressing, and hemolysis of tdh, trh and tlh genes of Vibrio parahaemolyticus

Abstract: Vibrio parahaemolyticus (VP) is one of the pathogenic vibrios endangering net-cage cultured Pseudosciaena crocea, Fennerpenaeus chinensis, and shellfish in coastal areas of China. Several types of hemolysins produced by Vp have been characterized as major virulence factors. They are thermostable direct hemolysin (TDH), TDH-related hemolysin (TRH) and thermolabile hemolysin (TLH). In this study, we cloned tdh, trh, and tlh genes from the genome DNA of VP by polymerase chain reaction (PCR). We ligated the three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 23 publications
0
13
0
1
Order By: Relevance
“…However, identifying the pathogenic serovars of V. parahaemolyticus by use of only these two toxins is not sufficiently accurate, as other hemolysins may take part in the pathogenicity of V. parahaemolyticus. Thermolabile hemolysin (TLH), a toxin encoded by the tlh gene of V. parahaemolyticus and present in almost every clinical and environmental V. parahaemolyticus strain (14, 37), has been suggested as a promising target for pathogen detection (30,35,44). Although TLH has hemolytic activity and can lyse red blood cells, its cytotoxic and biochemical mechanisms of action are still not clearly understood (3,26,31).…”
mentioning
confidence: 99%
“…However, identifying the pathogenic serovars of V. parahaemolyticus by use of only these two toxins is not sufficiently accurate, as other hemolysins may take part in the pathogenicity of V. parahaemolyticus. Thermolabile hemolysin (TLH), a toxin encoded by the tlh gene of V. parahaemolyticus and present in almost every clinical and environmental V. parahaemolyticus strain (14, 37), has been suggested as a promising target for pathogen detection (30,35,44). Although TLH has hemolytic activity and can lyse red blood cells, its cytotoxic and biochemical mechanisms of action are still not clearly understood (3,26,31).…”
mentioning
confidence: 99%
“…They have all been included in the tdh family because the coding sequences of these genes share >93% homology. [ 33 ] Clinical samples from an outbreak of gastroenteritis in the Republic of Maldives presented KP-negative strains of V. parahaemolyticus . However, these strains were found to express a new hemolysin, termed as TRH.…”
Section: Toxinsmentioning
confidence: 99%
“…[ 29 ] It should not escape our notice that V. parahaemolyticus bacteria express an additional toxin, known as thermolabile hemolysin (TLH). [ 33 ] It is encoded by the tlh gene, which is targeted during the genetic detection of V. parahaemolyticus because it is a species-specific marker. [ 13 ] TLH exhibits phospholipase activity and the ability to lyse human erythrocytes.…”
Section: Toxinsmentioning
confidence: 99%
See 1 more Smart Citation
“…Shinoda et al (1991) first reported the recombinant production of VpTLH as an active soluble protein from the periplasm of E. coli (Shinoda et al, 1991). Recombinant hemolysins TDH, TRH, and TLH from Vp also were expressed as inactive form and renatured by carbamide gradient dialysis (Zhao, Tang & Zhan, 2011). Despite these differences, recombinant VpTLH showed lecithin-dependent phospholipase and hemolytic activity as other Vibrio TLHs (Jia, Woo & Zhang, 2010;Li, Mou & Nelson, 2013;Zhao, Tang & Zhan, 2011).…”
Section: Discussionmentioning
confidence: 99%